Influence of Manual and Chemical Thinning on Yield and Quality of Nectarine [Prunus persica (L.) Batsch var. nucipersica] cv. Snow Queen - Kumar, Rajiv; Rimpika; Sharma, N.; Shylla, Bunty; Thakur, Anju; Sharma, D. P. (International Journal of Bio-resource and Stress Management, 2017)
Stone fruits have been found to be highly suitable to the mid hill zone of Himachal Pradesh. Among these fruits, nectarine is fast emerging as one of the important and potential fruit due its attractive appearance and better remuneration as compared to peaches. Among the various cultivars of nectarines being cultivated in this Zone, Snow Queen is the most important cultivar. But under congenial agro climatic conditions, it invariably bears copiously resulting in small to medium sized fruits which consequently fetches low price in the market. Hence the present studies have been carried out with the objective to study the influence of manual and chemical thinning on the fruit yield and quality of Snow Queen Nectarine during 2012 and 2013. Experimental trees were subjected to different treatments viz. retention of 3, 4 and 5 fruits manually, foliar application of Ethrel at 200 and 300 ppm, NAA at 20 and 40 ppm, TDZ at 20 and 40 ppm, Ethrel at 200 ppm+NAA at 20 ppm, Ethrel at 200 ppm+TDZ at 20 ppm and control (water spray) two weeks after petal fall, with three replications using RBD. Hand thinning to retain 3 fruits shoot-1 registered the highest thinning percentage, fruit size, weight and volume with the lowest yield. The fruits of the trees treated with Ethrel at 300 ppm recorded the highest content of TSS, total sugar, reducing sugar as well as fruit colouration while fruit acidity and firmness were the lowest in these fruits.